2001
DOI: 10.1034/j.1600-079x.2001.300104.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes of serum melatonin level and its relationship to feto‐placental unit during pregnancy

Abstract: Serum melatonin concentrations were studied in normal pregnant women and in women with several types of pathologic pregnancies, e.g., twins, preeclampsia or intrauterine growth retardation (IUGR). Blood samples were collected from the maternal antecubital vein at 14:00 hr (daytime) and 02:00 hr (nighttime) during pregnancy, and also from the umbilical vein and artery immediately after delivery. Serum melatonin concentrations were measured by radioimmunoassay. Daytime serum melatonin levels in normal (single fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
164
6
15

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(199 citation statements)
references
References 24 publications
11
164
6
15
Order By: Relevance
“…Although there was no statistical significance, the aMT6s levels of the pregnant subjects were apt to be higher than those of the non-pregnant. The same tendency was reported in other articles 25,26) . However, the association of melatonin secretion with reproductive function such as pregnancy remains unestablished 19) .…”
Section: Amt6ssupporting
confidence: 77%
See 1 more Smart Citation
“…Although there was no statistical significance, the aMT6s levels of the pregnant subjects were apt to be higher than those of the non-pregnant. The same tendency was reported in other articles 25,26) . However, the association of melatonin secretion with reproductive function such as pregnancy remains unestablished 19) .…”
Section: Amt6ssupporting
confidence: 77%
“…The change in melatonin level with advancing gestational age is also controversial. Some researchers have reported that melatonin levels might be altered during gestation 26,27) , while others reported unaltered 9,28) . As for this study on urinary metabolites, aMT6s, it displayed no significant alterations from the G1 when the subjects were on work to the G4 when out of work.…”
Section: Amt6smentioning
confidence: 99%
“…Our current findings confirm and extend our earlier report 8 showing that nocturnal melatonin AUC increased across weeks of pregnancy in HW but not in DW. Nakamura et al 27 also found that serum melatonin level increased as gestation progressed in normal pregnant women. Thus, E 2 and P 4 may be part of an important mechanism associated with increased melatonin quantity during pregnancy in HW.…”
Section: Posadas Et Almentioning
confidence: 88%
“…This suggestion is of note following the proposed general model pertaining to the onset and progression of childhood leukaemia which assumes that any initial event(s) occurs in utero (Greaves, 1999) (Chapter 1.2). While the same is potentially true in pregnant women where Nakamura et al (2001) illustrated that serum melatonin possesses a diurnal rhythm which rises substantially following 24 weeks gestation and remains elevated until the full term. Indeed the addition of radical scavengers and antioxidants were able to inhibit an ELF-MF related increase in cell proliferation (Wolf et al, 2005), the MFinduced production of superoxide radical anions (Mannerling et al, 2010) and also prevent the previously observed induction of single-and double-strand breaks in brain cells of rats following ELF-MF exposure .…”
Section: Radical Pair Mechanismmentioning
confidence: 97%